Analyzing Soundness in Financial Performance of Banque Pour Le Commerce Exterieur Lao Public (BCEL) by using A CAMEL Model - PHILASOUK, Thatsaphone; YANGSANSAY, Chahue; PATHOUMTHONG, Santi; PHANTHOULACK, Ounheuan (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
currently economic conditions in Lao People Democratic Republic (Lao PDR) in the world have encountered with a fluctuation. Business competition, Natural disasters, the spread of COVID- 19 and uncertainty in Business environment the particularly affected the financial performance of Banque Pour Le Commerce Exterieur Lao Public (BCEL). This means BCEL is required to improve the service process by applying modern technology and update the vision to become strong, modern and moving toward international standards and comply with CAMEL + Basel II principles. This research Analyzed financial performance of BCEL from 2015 to 2019 by using CAMEL model, which is based standard of capital Adequacy, Asset Quality, Management Efficiency, Earing Quality and Liquidity. The objectives of the study is to measure the financial performance of BCEL by comparing with B O L I n d i c a t o r s e t , and also uses secondary data from income statement and balance sheet of BCEL from 2011 to 2019. The study found that BCEL’s financial performance has sufficient Capital Adequacy from 2011 to 2019 due to Regulatory Capital to Risk Weighted Assets ratio, Regulatory Tier1 Capital to Risk Weighted Assets ratio and Asset Growth Rate is better than the BOL ratio set. The management of Asset Quality was great because BCEL has the ability to collect Non or Performing Loans (NPLs) or NPLs to Loan Ratio was greater than the BOL ratio set. However, BECL should have security net against Loan risk. Management Adequacy was also manageable because the Net Profit Margin and Profit Per Share was consistent with the investment. Return on Asset was lower than BOL ratio set, but Return on Equity was better than the BOL ratio set. BCEL also has high liquidity which has the ability to pay short-term debt. This is because Cash to Deposit Ratio, Loan to Deposit Ratio and Deposit Growth Rate was better than the BOL ratio set . This ratio showed BCEL’s liquidity by taking customer’ deposit account to credit provide.